Transurethral versus suprapubic catheter at robot-assisted radical prostatectomy: a prospective randomized trial with 1-year follow-up - Martinschek, Andreas; Pfalzgraf, Daniel Philipp; Ritter, Manuel; Heinrich, Elmar; Trojan, Lutz (World journal of urology, 2016)
Objective: To evaluate urethral catheter (UC) versus suprapubic tube (SPT) without stenting the anastomosis at robot-assisted radical prostatectomy (RALP) regarding surgical outcome and catheter-associated discomfort. One year after surgery, continence and patient satisfaction were evaluated. Materials and methods: Sixty-two patients undergoing RALP were prospectively randomized to urinary drainage with UC or with SPT. Functional results were assessed with standardized questionnaires (IPSS, IPSS Bother Score, IIEF and Visual Analogue Scale) preoperatively, after catheter removal and 1 year after surgery. Moreover, bother by the catheter as well as pain due to the catheter was assessed. Results: At personal hygiene, SPT was significantly less bothersome on the day of surgery as well as POD 1-6. Pain caused by the catheter did not differ significantly between the two groups except for POD 5 and 6, when the SPT performed significantly better. Differences regarding voiding parameters after catheter removal did not reach statistical significance. One year after surgery, no significant difference between the two groups was found regarding urinary function and IPSS. Though not statistically significant either, the need for the incision of bladder neck contracture (BNC) in two patients in the UC group is of note, as in the SPT group, no BNC occurred. Conclusion: Draining the bladder with SPT only is a feasible option in patients undergoing RALP. Patients with SPT are significantly less bothered by the catheter at personal and genital hygiene compared to UC. The risk of BNC seems to be reduced in the SPT group.